Hubungan Cyberloafing Dengan Prokrastinasi Kerja Pada Pegawai Kantor Dinas Kependudukan Dan Catatan Sipil (Dukcapil) Kabupaten Rejang Lebong - Janusi Waliamin; Putra, Okka Adittio (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2024)
The purpose of this research is to determine the relationship between cyberloafing and work procrastination among employees of the Civil Registration and Population Office in Rejang Lebong Regency. This study employs a quantitative approach with statistical data analysis. The population of the study consists of 27 individuals, and the sampling method used in this research is saturation sampling. Data were collected through observation, questionnaires, books, articles, and the internet. The results of the research, analyzed using SPSS version 26, show a highly significant relationship between cyberloafing and work procrastination among employees of the Civil Registration and Population Office in Rejang Lebong Regency. The limited number of employees in the Civil Registration and Population Office in Rejang Lebong Regency, which totals only 27, posed a challenge in data processing. This research can serve as a basis for consideration for the Civil Registration and Population Office in Rejang Lebong Regency to monitor and use office facilities, especially the internet, in accordance with their intended purpose.